Quality of life and handling experience with the PROSE device: an Indian scenario - Bhattacharya, Pradipta; Mahadevan, Rajeswari (Clinical and experimental optometry, 2017)
PROSE (prosthetic replacement of ocular surface ecosystem) device is a custom-designed, corneal vaulting scleral contact lens, which is used in the treatment of irregular corneal conditions to improve vision and comfort. The present study aimed at assessing the success of the device in an Indian scenario in terms of change in quality of life and to understand the handling issues related to the device use. Thirty-two subjects with various irregular corneal conditions meeting the inclusion criteria were included in the study. Subjects were followed for three months after dispensing the PROSE device. Subjects' demographic details, high and low contrast visual acuity with habitual correction and PROSE device, Visual Function Questionnaire scores (NEI VFQ-25) and Ocular Surface Disease Index (OSDI) scores pre- and post- PROSE treatment were collected and compared. An indigenously developed questionnaire was also administered during the follow-up visit for assessing the handling-related issues faced by the subjects while using the device. Forty eyes of 32 subjects were included in the study, of whom 30 reported for follow-up. The median NEI VFQ-25 score improved from 47.33 points to 77.27 points over a period of three months, which was statistically significant (p < 0.05). There was a statistically significant decrease in median OSDI score from 51.14 points to 13.63 points post-PROSE treatment (p < 0.05). Subjects reported no or very minimal handling-related difficulties associated with the use of the PROSE device. The PROSE treatment can be an effective mode of managing patients with irregular corneal conditions and significantly improved the vision-related quality of life of patients suffering from these conditions. The handling of the device is easy and can be mastered with adequate training.